Elements for identification of the prohibited practices in ecquines - Cristina, T. Romeo,; Alina Netotea,; Diana Iacob–Obistioiu,; Flavia Hanganu (Medicamentul Veterinar, 2009)
In the Romanian veterinary medicine, animal doping, in the one hand, has not yet been so expanded like in the developed countries, where equestrian sports practice are known for long time, the lack of sustained national activities in this area and the other hand due to lack of material means. However the development of dog breeding and of the equestrian sports will undoubtedly make place for fraud. Medicines or medications have been tested in horse racing since 1903. Today racehorses testing for the identification of the prohibited substances are by far the oldest, largest and most sensitive way fordetermination of drug testing. Tests on doped horses are conducted under strict regulatory context and extremely precise. Although isknown the fact that drugs can affect in a decisive way the performances of the race horses, though scientific evidence found in the literature to support this are still relatively poor. This report introduces in Romania the elements of identification and prevention of illegal practices in sport horses.